Highly efficient chemoselective hydrogenation of 5-HMF to BHMF over reusable bimetallic Pd-Ir/C catalyst - Ratrey, Geetanjali; Solanki, Bhanupratap S.; Kamble, Sanjay P.; Rode, V. Chandrashekhar (ChemistrySelect, 2022)
Catalytic synergism was observed for a bimetallic Pd-Ir catalyst supported on activated carbon for chemoselective hydrogenation of 5-hydroxymetahyl furfural (5-HMF) to 2, 5-(bishydroxymethyl) furan (BHMF) with complete conversion and 97 % selectivity under very mild reaction conditions. The structural characterization like XRD, N-2 sorption, FE-SEM and TEM suggested formation of fine nanoparticles (1.95-3.08 nm) having very higher surface area, uniform distribution and mesoporous nature of the material. XPS spectra and Pyridine-IR spectroscopy revealed formation of Pd-PdO and Ir/IrO2/IrO3 interface on the catalytic surface along with strong Bronsted acidic sites which were responsible for high efficiency of catalyst at 80 degrees C, 100 psig H-2 pressure at 5-HMF/Catalyst=20 and within 2.5 h of reaction time. A plausible reaction mechanism is also elucidated based on structure activity correlation.
Keywords: 5-HMF; Carbon; Catalytic synergism; Selective hydrogenation; Valorization

Selective oxidation of 5-HMF to DFF over alkali promoted Mn nanocomposite - Solanki, Bhanupratap Singh; Roh, Hyun-Seog; V. Rode, Chandrashekhar (Applied Catalysis A-General, 2023)
Various compositions of Cs promoted Mn catalysts were synthesized and investigated for selective oxidation of 5HMF to DFF, among which Mn-Cs(80:20) was found to be most efficient giving 91 % conversion of 5-HMF and 99 % selectivity to DFF. Detail characterization like N2-sorption, BET surface area, TG-DTA, XRD, XPS, FE-SEM-EDX, TEM, HR-TEM, CO2-TPD, H2-TPR, O2-TPO, FTIR, Raman spectra and CH3OH-IR were done to establish structureactivity correlation. Enhanced surface area, porosity, thermal stability, dual morphologies were observed due to inclusion of Cs in Mn lattice domain which further enhanced the crystallinity, and oxygen diffusion on the surface. Mixed morphologies comprising nanoparticles (4-5 nm) and nanocubes (50-60 nm) were observed with enhanced redox potential and reduced work function due to weakening of Mn-O bonds. Significant increase in the basicity of catalyst, interfacial redox properties and lattice oxygen led to highly efficient oxidation of 5-HMF to DFF via Mars-van Krevelen mechanism at relatively milder conditions i.e. T = 90 degrees C and PO2= 200 psig. The catalyst was easily recyclable up to 7 times with minor loss in activity which was regenerated heat treatment protocol.
Keywords: 5-HMF; Biomass; heterogeneous catalyst; polyurethane; Selective oxidation